(3GdhLjR aj GdTQcGJ GdJLGQjI hGdEadGSs - (3CSGeI fGFd(B, (3GdeMjSfs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2008)
(3jVe GdTQcGJ, GdCMcGe GdYGeI ddTQcGJ, TQcGJ GdCTNGU, TQcGJ GdCehGd, GdTQcGJ PGJ GdWHjYI GdeNJdWI, GdGadGS, GdUdM GdhGbj ddGadGS, TgQ GdEadGS, Mdhd bVGjG GdJadjSI, GYGOI GdEYJHGQ GdEadGSjs
(3GdeQGLY U(B.395s
Keywords: (3GdEadGSs; (3GdTQcGJs; (3GdTQcGJ GdJLGQjIs